Metformin Protects Cardiovascular Health in People With Diabetes - Chen, Chong; Yuan, Shiqi; Zhao, Xuenuo; Qiao, Mengmeng; Li, Shuna; He, Ningxia; Huang, Liying; Lyu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Metformin is the most commonly used drug for patients with diabetes, but there is still some controversy about whether it has a protective effect on cardiovascular health. We therefore used the National Health and Nutritional Examination Survey (NHANES) database to analyze the impact of metformin use on cardiovascular health in patients with diabetes. Methods: We extracted the demographic data and laboratory test results of all people with diabetes in the NHANES database from January 2017 to March 2020. The outcomes were seven indicators of cardiovascular health from the American Heart Association, each was scored as 0, 1, and 2 to represent poor, moderate, and ideal health statuses, respectively. The scores for the indicators (excluding diet and glycemic status) were summed, and the sum score was then considered to indicate unhealthy (0–5) or healthy (>5). Multivariate logistic regression analysis was used, and subgroup analyses were performed by age, alcohol consumption, education, and marital status. Results: This study included 1356 patients with diabetes, among which 606 were taking metformin. After adjusting for all included variables, oral metformin in patients with diabetes had a protective effect on the cardiovascular health of patients (OR=0.724, 95% CI=0.573–0.913, P=0.007). Subgroup analysis indicated that metformin protects the cardiovascular health of people with diabetes more clearly in those who are young (OR=0.655, 95% CI=0.481–0.892, P=0.007), married (OR=0.633, 95% CI=0.463–0.863, P=0.003), and drink alcohol (OR=0.742, 95% CI=0.581–0.946, P=0.016). Conclusion: This study found that metformin has a protective effect on the cardiovascular health of patients with diabetes. The study findings support the general applicability of metformin.